Development of automated fruit Grading system using vision and Artificial intelligent technique. - Muhamad Amin Zunaidi B. Zainal Abidin (School of Computer and Communication Engineering, University Malaysia Perlis, 2015)
Fruit grading system is a system to identify the level of maturity of the fruit using image processing techniques. This system is used to streamline grade fruit with fruit isolated in three groups: unripe, ripe and overripe. Fruits can be classified by distinguishing colour, so colour is one of the important criteria in this system. The method used in this system is using the method of image processing with RGB colour histogram method. Issues regarding the grading system using human Visualization System also completed. Manual grading system costs, time to grading fruits and employment reduced.